2006
DOI: 10.2320/jinstmet.70.534
|View full text |Cite
|
Sign up to set email alerts
|

Pitting Corrosion Resistance of Anodized Aluminum Alloy Processed by Severe Plastic Deformation

Abstract: The effect of equal channel angular pressing (ECAP) on the pitting corrosion resistance of anodized Al and Al Mg alloy was investigated by electrochemical techniques in a solution containing 0.25 mol/L of AlCl 3 and by surface analysis. The time required before initiating pitting corrosion of anodized Al was longer with ECAP than without, indicating improvement in the pitting corrosion resistance by application of ECAP. However, in anodized Al Mg alloy, the pitting corrosion occurred earlier with ECAP than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…10,11) As can be seen from Fig. 8, the compressive stress in anodic oxide films of Al-Mg alloy was larger with ECAP than without.…”
Section: Effect Of Ecap and Annealing On The Internal Stress In Anodimentioning
confidence: 59%
See 2 more Smart Citations
“…10,11) As can be seen from Fig. 8, the compressive stress in anodic oxide films of Al-Mg alloy was larger with ECAP than without.…”
Section: Effect Of Ecap and Annealing On The Internal Stress In Anodimentioning
confidence: 59%
“…The pitting corrosion of Al is reported to originate around these precipitates not oxidized. 10,11) It is clear that the pitting corrosion originates around the precipitates and generates cracks through the pitting area in the anodic oxide films, as shown in Fig. 6.…”
Section: Morphology Of the Pitting Areamentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, authors have already reported that the pitting corrosion resistance of Al-Mg alloy after anodization was worse with ECAP than without. 11,12) This suggests that the effect of ECAP on the pitting corrosion resistance of anodized Al alloys changes according to the kind of alloying elements. The time to pitting corrosion of anodized Al-Cu alloy increased with increased anodizing current density.…”
Section: Resultsmentioning
confidence: 99%
“…Authors reported previously that the pitting corrosion resistance of Al and Al-Mg alloy was improved by ECAP, but the corrosion resistance of anodized Al-Mg alloy was worse with ECAP than without. [9][10][11][12] The pitting corrosion resistance of anodized Al alloys depends on the alloying elements, and the effect of ECAP on the pitting corrosion resistance also seems to change according to the kind of alloying elements. In this study, copper was selected as the alloying element, and the effect of ECAP on the pitting corrosion resistance of anodized Al-Cu alloy processed by ECAP was investigated using electrochemical techniques.…”
Section: Introductionmentioning
confidence: 99%